2016
DOI: 10.1108/wjemsd-02-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and employee turnover intention

Abstract: Purpose – The purpose of this paper is to investigate the impact of transformational leadership on employee turnover intention through the mediating role of affective commitment. Design/methodology/approach – The study examines conceptual relationships in the Ghanaian context, based on structural equation modelling with maximum likelihood estimation, using sample employees from the private sector organizations. In addition, the mediation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(146 citation statements)
references
References 103 publications
15
106
1
9
Order By: Relevance
“…[51]also found that transformational leadership affect the turnover intention. In contrast, [46] found that transformational leadership did not affect the turnover intention in Ghana. Leadership style (transformational and transactional) was proposed to affect the turnover intention in manufacturing companies in Malaysia.…”
Section: Leadership Style and Turnover Intentionmentioning
confidence: 75%
See 1 more Smart Citation
“…[51]also found that transformational leadership affect the turnover intention. In contrast, [46] found that transformational leadership did not affect the turnover intention in Ghana. Leadership style (transformational and transactional) was proposed to affect the turnover intention in manufacturing companies in Malaysia.…”
Section: Leadership Style and Turnover Intentionmentioning
confidence: 75%
“…The authors pointed out that implementing transformational leadership in public sector is challenging due to the complex environments of this sector and the need to take into consideration the legal, regulatory, and policy demand. Nevertheless, researchers have deployed the transformational and transactional leadership to understand their effects on the turnover intention in public sector [43], [44] and on work attitude in private sector [13], [45], [46]. This study deployed the theory of transformational and transactional leadership to explain the effect of leadership styles on turnover intention.…”
Section: Leadership Stylementioning
confidence: 99%
“…Hasil yang ditemukan oleh Sartika (2014) keinginan keluar karyawan lebih dipengaruhi oleh komitmen bersinambungan seperti nilai ekonomi yang dirasa dari bertahan di perusahaan dibandingkan dengan komimen afektif dan komitmen normatif seperti persepsi terhadap gaya kepemimpinan transformasional. Berbeda dengan hasil penelitian yang dilakukan oleh Gyensare et al (2016) bahwa komitmen afektif memiliki dampak positif terhadap pengaruh kepemimpinan transformasional terhadap turnover intention dimana jika organisasi peduli dengan karyawannya maka sebaliknya karyawan akan merawat organisasi tersebut sebagai timbal balik dari ikatan emosional mereka.…”
Section: Gambar 1 Kerangka Konseptual Penelitianunclassified
“…Berbeda dengan hasil penelitian yang dilakukan oleh Gyensare et al (2016) bahwa komitmen afektif memiliki dampak positif terhadap pengaruh kepemimpinan transformasional terhadap turnover intention dimana jika organisasi peduli dengan karyawannya maka sebaliknya karyawan akan merawat organisasi tersebut sebagai timbal balik dari ikatan emosional mereka. Penelitian yang dilakukan Gatling et al (2016) menemukan bahwa kepemimpinan memiliki pengaruh negatif tidak langsung dan signifikan terhadap turnover karyawan dengan komitmen organisasional sebagai mediasi, dimana hubungan ini dijelaskan oleh sejauh mana karyawan memiliki ikatan emosional dengan organisasi dan sejauh mana karyawan tidak puas dengan pekerjaannya.…”
Section: Hasil Dan Pembahasanunclassified
“…Studies (e.g. Caillier, 2016;Green, Miller, & Aarons, 2013;Gul, Ahmad, Ur Rehman, Shabir, & Razzaq, 2012;Gyensare, Olivia Anku-Tsede, Sanda & Okpoti, 2016;Sahu, Pathardikar & Kumar, 2018;Wells & Peachey, 2011) made findings pointing to the relationship between the transformational leadership style and employee retention. For instance, Caillier (2016) reported a direct negative association between transformational leadership and turnover intentions.…”
Section: Introductionmentioning
confidence: 99%